Sources of risk and uncertainty in UK smart grid deployment: An expert stakeholder analysis. (15th October 2018) - Connor, P.M.; Axon, C.J.; Xenias, D.; Balta-Ozkan, N.
Abstract: The shift to increasingly smarter grids will require preparation and planning on the part of a diverse selection of current and future stakeholders. There are substantive sources of uncertainty that will impact on the adoption of smarter grid solutions. Risks and uncertainties are placed in one of seven categories: markets, users, data and information, supply mix, policy, investment conditions, and networks. Each of these has the potential to add risk to the planning profiles of the stakeholders involved. Here, UK stakeholders drawn from industry, government, regulators, and academia are canvassed about potential sources of uncertainty within the UK's electricity sector and the attendant risks that might be engendered by them. Highlights: Stakeholders identified risk sources which might hinder growth of UK smart grids. Risks linked to uncertainty in smart grid development are discussed. Seven groups of risks and uncertainties are identified. Stakeholders identified four cross-cutting issues as barriers to UK smart grids. The smart grid is not a single endpoint, networks will become incrementally smarter.